Investigation of wear characteristics of Fe/ferrochromium composite which is obtained by powder metallurgy - Yilmaz, Osman; Aksoy, Mustafa; Yildirim, Süleyman (My University, 1999)
In this study, wear characteristics of composite produced from addition of ferrochromium powders to iron powders has been aimed. For this reason, iron powders mixed with ferrochromium powders in % 5, 7, 10 ranges. Samples were sintered at 1200°C temperature and 2 hour. At the end, a composite material having ductile matrix, which is obtained by iron powders, and hard particles by ferrochromium particles have been produced Sintered samples have been investigated by E.D.S analysis. As an another sequences, for metallographic studies, optical microscope and SEM have been used. Using different loading wear tests have been applied. Results of test have been discussed considering ferrochromium range and metallographic structure. Results have shown that the sample with %5 ferrochromium have given the least wearing value and the same with %10 ferrochromium sample have given the most wear value. Moreover, ferrochromium particles were mixed as %5 and %10 to PVC for producing a composite having soft matrix with hard particles for proving wearing results. It was seen that between results of samples, there is similarity.
Toz metalurji?si? i?le üreti?len Fe/ferrokrom kompozi?ti?ni?n aşinma karekteri?sti??i?ni?n i?ncelenmesi?
Ulusal Toz Metalurjisi Konferansi: Second National Powder Metallurgy Conference -- 15 September 1999 through 17 September 1999 -- Ankara -- 62638
Keywords: Abrasive wear; Composites; Sintering